An empirical analysis of the relationship between university investments in Technology Transfer Offices and academic spin‐offs. (27th September 2020) - Iacobucci, Donato; Micozzi, Alessandra; Piccaluga, Andrea
Abstract : The aim of this paper is to analyze the role of university Technology Transfer Offices (TTOs) in contributing to the creation and the performance of academic spin‐offs (ASOs). More specifically, it investigates the relationship between resources invested in TTOs in term of employees and the creation and growth of ASOs. The empirical analysis refers to Italy, where since 1999 academicians have been allowed to be actively involved in setting up companies for the 'industrial use of research'. We used data on ASOs and resources invested by Italian universities in TTOs during the 2002–2011 period to investigate if and to what extent such investments contributed to the birth and growth of ASOs. We also controlled the results using information on university and on local context, in which university is located. The results of the empirical analysis show that in a first phase academicians reacted more promptly than universities to the opportunities offered by the new legislation, which may in part be due to the organizational rigidity that characterizes Public Administration in Italy. However, the empirical analysis also shows that after this initial phase the size of the TTOs (in terms of employees) has had a positive influence on the number of new ASOs (i.e. birth), but not on the performance of ASOs (i.e. growth), which is influenced by both long‐term investments in research (i.e. the quality of research results) and other variables linked to the regional and national contexts, such as the presence of incubators or the level of economic development. Our results regard a widely studied topic and should provide incremental findings for the community of entrepreneurship scholars and relevant implications for policy makers and TTO managers.